PRECIPITATING FACTORS AND CLINICAL PRESENTATION AT THE TIME OF ADMISSION FOR DIABETIC KETOACIDOSIS IN NANGARHAR AFGHANISTAN - I. Ikramullah Ibrahimi; Hayatullah Ahmadzai; Salam Jan Shams (Interdisciplinary Approaches to Medicine, 2024)
The aim of the study was to determine the frequency of different DKA precipitating factors and the initial clinical feature at the time of admission. This descriptive prospective cross sectional study based on purposive sampling, was conducted in the medical ward of Nangarhar University Teaching Hospital from 28/12/2019 to 10/2/2021 including both female and male patients of any type of DM with DKA at the time of admission. After thorough history taking, physical examination and investigations such as lab, radiological and ECG, precipitating factors were found out.